대장암 세포주 SNU C2A에서 etoposide 처리에 의한 apoptosis 유도 - 정지연(Ji-Yeon Jung); 나윤숙(Yun-sook Na); 정호철(Ho-Chul Jung); 오상진(Sang-Jin Oh) (Immune network, 2001)
Background: Inactivation of tumor suppressor genes is believed to be important in the development of many human malignancies. Recently, several lines of evidence have indicated that the wild type p53 gene located at 17p13.3, may function as a tumor suppressor gene and that a mutant p53 gene could promote transformation by inactivating normal p53 function in a dominant negative fashion. These broad spectrum of p53 mutation in human cancers provide that mutant p53 and their protein may be potential targets of tumor diagnostic and therapeutic interventions. Method: Colony formation was performed to investigate growth suppressional ability. p53 expression pattern was examined by western blot and p53-mediated transactivation ability was assessed by CAT activity. SNU C2A cells were observed in apoptotic aspects induced by etoposide and $H_2O_2$ treatment, detecting sensitivity on agent, DNA fragmentation through agarose gel, chromatin condensation by fluorescence microscope, and cell cycle distribution by FACS. Result: 1) p53 mutant his179arg ($histidine{→}arginine$) detected in SNU C2A cells lost transcriptional activity and growth suppression ability, showing dominant negative effect on its wild type p53. 2) Etoposide-treated SNU C2A cells induced apoptosis, exhibiting dramatic reduction of cell growth, DNA fragmentation, nuclear condensation formation of apoptotic body and increment of sub-G1 cell fraction. 3) Etoposide and $H_2O_2$-treated SNU C2A cells have no high increase of p53 expression and overexpressed p53 protein changed localization, from cytoplasm to nucleus. Also, p53-mediated transcriptional activity was increased by agents-treatment. Conclusion: SNU C2A cells coexpress wild-type and mutant p53 protein induced apoptosis in the condition on DNA damage, through localizational shift from cytoplasm to nucleus of p53 protein rather than the induction of p53 protein. SNU C2A cells derived mutant p53 his179arg abrogated both the growth supression ability and transactivational activity, showing inhibition effect on transcriptional activity of wild type p53, but did not repress the activity of wild type p53 in SNU C2A cells owing to dominant activity of wild type. These cell condition may provide new gene therapeutic implications leading effective antiproliferation of cell when mutant and wild-type p53 protein were co-expressed in cell.